Natural development of sprint speed in girls and boys: a narrative review - Talukdar, K.; Harrison, C.; McGuigan, M. R. (The Journal of Sport and Exercise Science, 2022)
Sprinting is a fundamental motor skill in many sports. The ability to move rapidly over short distances can significantly impact the outcome of a game. The natural development of sprinting speed is similar in females and males during the first decade of life. However, due to changes in hormonal levels during puberty the development of kinetic and kinematic variables associated with sprinting may be affected in young females compared to their male counterparts. Previously researchers have investigated sprinting kinetics and kinematics in young males. However, there is a paucity of research on young females. Therefore, the purpose of this review is to highlight the biological differences between genders with regard to sprinting and the changes in kinetics and kinematics across maturation in young females